2020
DOI: 10.3390/agronomy10020191
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Na+ Ratio as a Critical Marker for Field Evaluation of Saline-Alkaline Tolerance in Alfalfa (Medicago sativa L.)

Abstract: Current indices of saline-alkaline (SA) tolerance are mainly based on the traditional growth and physiological indices for salinity tolerance and likely affect the accuracy of alfalfa tolerance predictions. We determined whether the inclusion of soil alkalinity-affected indices, particularly Ca2+, Mg2+, and their ratios to Na+ in plants, based on the traditional method could improve the prediction accuracy of SA tolerance in alfalfa, determine important indices for SA tolerance, and identify suitable alfalfa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Alkaline stress not only inhibits the seed germination of alfalfa but also seriously affects the growth and development of seedlings (An et al 2016, Liu et al 2018, Long et al 2019. Our previous study also con rmed that the alkaline tolerance of alfalfa was associated with the cultivar's genetic characteristics (Wei et al 2020). As shown by our results, AG is more sensitive to alkaline stress than GN, as re ected by the decreased shoot fresh weight and leaf chlorophyll contents (Fig.…”
Section: Physiological Regulation In Response To Alkaline Stresssupporting
confidence: 76%
See 3 more Smart Citations
“…Alkaline stress not only inhibits the seed germination of alfalfa but also seriously affects the growth and development of seedlings (An et al 2016, Liu et al 2018, Long et al 2019. Our previous study also con rmed that the alkaline tolerance of alfalfa was associated with the cultivar's genetic characteristics (Wei et al 2020). As shown by our results, AG is more sensitive to alkaline stress than GN, as re ected by the decreased shoot fresh weight and leaf chlorophyll contents (Fig.…”
Section: Physiological Regulation In Response To Alkaline Stresssupporting
confidence: 76%
“…3). Interestingly, GN maintained higher accumulation of Ca 2+ and Mg 2+ , and the ratios of these two ions to Na + in shoots were also higher than those in AG, suggesting that accumulation pro les of Ca 2+ and Mg 2+ may play an important role in maintaining ionic homeostasis in alfalfa under alkaline stress (Wei et al 2020). Based on the above results, we speculate that the transient increase in Ca 2+ levels of alkalinetreated plants might activate alkaline signaling pathways in the plant and be involved in regulating anti-stress genes expressed in response to alkaline stress.…”
Section: Physiological Regulation In Response To Alkaline Stressmentioning
confidence: 94%
See 2 more Smart Citations
“…In China, most alfalfa plantations are located in regions with saline-alkali soil due to the lack of farmland [ 44 ]. An urgent and promising task for alfalfa production in the nation is to breed varieties with tolerance to high salinity [ 45 ]. Our prediction of the cis -elements present in the putative promoter region of the MsSPLs revealed that 89.4% of MsSPLs possessed ABA-responsive elements (ABREs) [ 46 ], suggesting a possible contribution to the alfalfa abiotic stress response.…”
Section: Discussionmentioning
confidence: 99%